AN ANALYSIS OF LANGUAGE LOSS IN “BURNT SHADOWS”: AN INQUIRY INTO LINGUISTIC DIVERSITY AND IMPERIALISM - Sana Zafar; Dr. Aftab Akram (International Journal of Contemporary Issues in Social Sciences, 2024)
The research paper analyzed the process of language loss in Kamila Shamsie’s ‘Burnt Shadows’ and investigated the linguistic diversity and imperialism in the novel. The study explored the linguistic imperialism and its impact on characters from different cultural backgrounds through a detailed analysis of the description of the plot and character relations built in the novel. By invoking theoretical framework of Homi K. Bhabha’s hybrid identity and utilizing a qualitative approach, the analysis helped to reveal how language use and proficiency are used to represent authority and power within the story. The paper identified the instances of code-switching and linguistic hybridity which are used by the characters in order to deconstruct linguistic boundaries and questions of cultural identity when faced with imperialist pressures. In addition to citing Robert Phillipson and David Crystal, the research placed “Burnt Shadows” within the discussions on colonialism and the call for linguistic justice in post-colonial nations. In conclusion, this research helps to better explain language loss as a result of linguistic imperialism and the importance of maintaining language diversity in the world today.